Tradition-Aware Chaplaincy Theory (TACT): A Name Change for and Evolution of Religiously Informed, Relationally Skillful Chaplaincy Theory - Ragsdale, Judith R. (Journal of pastoral care & counseling, 2025)
Religiously Informed, Relationally Skillful Chaplaincy Theory (RIRSCT) (Ragsdale & Desjardins, 2020) is a chaplaincy theory positing that healthcare chaplains would be more helpful to patients and to members of the healthcare team if they were better versed in how patients’ religious beliefs and practices impacted their healthcare experience. Changing the theory's name to Tradition-Aware Chaplaincy Theory expands the original theory to include spiritualities and secular belief systems not included in the term “Religiously Informed.”